THE INFLUENCE OF THE INQUIRY BASED LEARNING MODEL IN STUDENTS MATHEMATICS LEARNING: A META-ANALYSIS - Purwantini; Joko Widodo; Agus Triyono; Arwaty; Siti Aisyah; Tomi Apra Santosa (Adisam Publisher, 2023)
The purpose of this study is to determine the reason for inquiry learning model for students' mathematics learning. This study is a meta-analysis study. The research data comes from 17 national and international journals published from 2015-2023. Data analysis in this study with the JSAP application. The inclusion criteria in this study are 1) research comes from journals or proceedings indexed by Scopus and SINTA; 2) The study has two experimental classes with inquiry-based learning models and conventional learning control classes; 3) journals or proceedings obtained from Google Scholar, AIP Proceedings, IOP Proceedings, Wiley, ERIC Journa and ScienceDirect. The results of the study concluded that the summary effect size or mean effect size value was 0.833 height criteria and values (Z = 9,061; p < 0.001). This finding explains that the inquiry-based learning model has a positive effect on students' mathematics learning compared to conventional models.